Investigating Prayer Impact on Health and Quality of Life - Olver, Ian.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
From the ancients to the Renaissance, religion and medicine worked hand in hand to heal the people, until the scientific minds of the Enlightenment created a physical model of illness without a spiritual component. In this century, spirituality is gaining recognition as part of individuals’ psychological makeup and capacity for meaning-making, and gaining currency as part of holistic concepts of wellness despite resistance from many in the scientific community. Prayer: Investigating Its Impact on Quality of Life brings science and spirituality together, pointing out thought-provoking parallels and asserting that each can enrich the other. At the book’s center is a detailed study of a randomized double-blinded trial that added intercessory prayer (i.e., prayer for others) to conventional cancer treatment, with findings relevant to conceptions of prayer as intervention. In addition, a review of salient medical literature (including complementary and alternative medical journals) contains both positive and negative studies, encouraging a vigorous dialogue about methodology, endpoints, and whether metaphysical phenomena can—or should—be studied using scientific methods. Among the topics covered: · The role of spirituality in illness. · Prayer as complementary or alternative therapy. · The relationship between spiritual wellbeing and quality of life. · Instruments for assessing religious and spiritual belief. · A randomized blinded study of intercessory prayer in patients with cancer. · Possible directions for further research. Prayer: Investigating Its Impact on Quality of Life should interest readers on all sides of the debate, including doctors, practitioners, psychologists, psychiatrists, and others involved in holistic treatment of patients.
Chapter 1. What is Prayer and Why Study it? -- Chapter 2. Studies of Prayer as a Complementary Therapy -- Chapter 3. A Theological Reflection on Prayer -- Chapter 4. The Relationship Between Spiritual Wellbeing and Quality of Life -- Chapter 5. A Randomized Blinded Study of Intercessory Prayer in Patients with Cancer -- Chapter 6. The impact of the study on the trials team -- Chapter 7. Response to our Study of Prayer -- Chapter 8. What next? .
Keywords: Quality of life; Health psychology; Complementary medicine; Psychotherapy; Counseling; Religion—Philosophy.; Quality of Life Research; Health Psychology; Complementary & Alternative Medicine; Psychotherapy and Counseling; Philosophy of Religion